Association Between Low Vitamin D Levels, Sleep During Pregnancy and Post-Delivery, Depressive and Anxiety Symptoms: Longitudinal Analysis of the NiPPeR Trial - Ciara McKay; Sheila Barton; David Baldwin; Keith Godfrey; Holly Austin (BJPsych Open, 2025)
Aims: Sleep is altered during pregnancy, particularly during the third trimester. Low Vitamin D levels have been linked to shorter sleep duration, depression and anxiety. In the NiPPeR double-blind randomised controlled trial of nutritional supplementation, women received either a formulation with additional ingredients including Vitamin D (‘intervention group’) or standard prenatal vitamins (‘control group’). The association between Vitamin D deficiency, sleep, depression and anxiety was examined from pre-conception to six months post-partum. We aimed primarily to determine if women deficient in Vitamin D (<50nmol/L) were more likely to have disordered sleep compared with those Vitamin D sufficient. A secondary aim was to examine if women deficient in Vitamin D were more likely to be depressed or anxious compared with those with adequate Vitamin D levels.